2011
DOI: 10.1188/11.onf.e418-e424
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Comprehensive Rehabilitation Program for Post-Treatment Patients With Cancer

Abstract: Multidisciplinary rehabilitation should become part of the total care plan for patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Three articles were identified through hand searching, leading to a total of 22 articles included. Sixteen articles [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] on the effectiveness of multidimensional cancer survivor rehabilitation were included, the data from which originated from 11 trials. The data from one of those trials were presented in two complementary articles [46,47] and the data from another trial were used in four articles [42][43][44][45].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three articles were identified through hand searching, leading to a total of 22 articles included. Sixteen articles [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] on the effectiveness of multidimensional cancer survivor rehabilitation were included, the data from which originated from 11 trials. The data from one of those trials were presented in two complementary articles [46,47] and the data from another trial were used in four articles [42][43][44][45].…”
Section: Resultsmentioning
confidence: 99%
“…Articles measuring subscales of fatigue (n ϭ 8) found statistically significant benefits, but not for all subscales [41,46] or for all measurements [37]. For physical outcome measures, such as muscle strength, physical functioning, and energy levels, 12 of 13 articles reported significant benefits [32,34,[37][38][39][41][42][43][44][45][46][47]. HRQoL and emotional, cognitive, psychological, and social outcome measures, however, varied strongly among studies, although none reported significant deteriorations.…”
Section: Effectiveness Of Multidimensional Interventionsmentioning
confidence: 99%
See 3 more Smart Citations